Evaluation of the electroflotation efficiency for the oil-containing shipping waters treatment - Марта Борисівна Вознюк; Тетяна Олександрівна Шаблій (Вісник Національного технічного університету України «Київський політехнічний інститут імені Ігоря Сікорського»: Серія «Хімічна інженерія, екологія та ресурсозбереження», 2023)
The article describes the problems of formation and purification of ship oil-containing waters. The effectiveness of electroflotation using aluminum and iron anodes for the extraction of oil from water-oil emulsions with different mineralization was assessed.